Examining alternative carbon resources for sustainable energy generation: A comprehensive review - Anjan Ray; Aman Kumar Bhonsle; Jasvinder Singh; Jayati Trivedi; Neeraj Atray (Next Energy)
ABSTRACT: The excessive usage and limited availability of fossil fuels have put enough impetus on researchers to find alternative energy sources to control the energy crisis and reduce climate change. To mitigate environmental impact while generating clean energy, researchers and energy experts are particularly focused on harnessing energy from bioresources and waste materials. This review article gives insight into various type of alternative fuels, their production strategies, and applications. Further, it explores the availability of domestic carbon resources like agroforestry, nonfood energy crops, municipal solid waste, agro-industry waste, food waste, wastewater, and anthropogenic-generated wastes from various industries. Furthermore, the potential for making alternative fuels like biodiesel and bioethanol adopts sustainable biochemical processes like aerobic and anaerobic digestion, fermentation, and methanation. Landfill processes and thermal processes like gasification, and pyrolysis are also explored to harness the waste streams into alternative energy sources, promising environmental benefits.